HUBUNGAN PENGETAHUAN PERAWATAN RAMBUT PASCA PELURUSAN (REBONDING) DENGAN KESEHATAN RAMBUT MAHASISWA JURUSAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - Sari, Rika Mailan; Rostamailis, Rostamailis; Astuti, Murni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aimed to describe hair treatment done by the students of Family Welfare Department, Faculty University of Padang who has done hair straightening (rebonding). This research is a correlation with the population of 45 people and the samples were 45 students who have been doing hair straightening (rebonding). The sample in this study was done by using purposive sampling. Data collection techniques using Likert Scale and Scale questionnaire Guttman already tested for validity and reliability. Data analysis using descriptive analysis was done by testing normality and linearity test, hypothesis testing with product moment correlation. Based on the results of the data proving that the students from the Department of Family Welfare Faculty of Engineering, University of Padang; (1) hair care knowledge possessed by students who have been doing hair straightening medium category with the percentage of 33,33%, (2) Health student who has been doing hair straightening (rebonding) including category simply by 64.12% percentage, (3) There is a significant relationship between health care done by students who have hair straightening (rebonding) with evidentiary value 0.241> 0.5 in the low category.Keywords : Knowledge Hair Treatmen After Straightening, Hair Health